A contribution to the knowledge of New World Bruchinae (Coleoptera, Chrysomelidae): taxonomic revision of Ctenocolum Kingsolver & Whitehead, with description of five new species - de Albuquerque, Felícia Pereira; Manfio, Daiara; Ribeiro-Costa, Cibele Stramare (Zootaxa, 2014)
The aim of this contribution was to review the species of Ctenocolum which are mainly distributed in the Neotropical region. The larvae of this genus have a high degree of specificity with the tribe Millettieae feeding mainly on seeds of Lonchocarpus Kunth (Fabaceae, Papilionoideae) and until now we do not know other bruchine consuming seeds of this genus. Here 13 valid species were studied, five new, divided in two groups, as previosly proposed in literature, group podagricus with Ctenocolum aquilus Albuquerque & Ribeiro-Costa sp. nov., C. biolleyi Kingsolver & Whitehead, C. colburni Kingsolver & Whitehead, C. martiale Kingsolver & Whitehead, C. milelo Albuquerque & Ribeiro-Costa sp. nov., C. podagricus (Fabricius), C. punctinotatus Albuquerque & Ribeiro-Costa sp. nov., C. pygospilotos Albuquerque & Ribeiro-Costa sp. nov. and C. triangulatus Albuquerque & Ribeiro-Costa sp. nov.; group tuberculatum with C. acapulcensis Kingsolver & Whitehead, C. janzeni Kingsolver & Whitehead, C. salvini (Sharp) and C. tuberculatum (Motschulsky). A lectotype is designated for Bruchus salvini and Bruchus pictifemur. Moreover, descriptions, redescriptions, diagnoses, key, geographic distribution and host plant records are also included.